The Narcotics Abuse Rehabilitation for Police Members by the National Narcotics Agency (BNN) - Avrila Anzani (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2022)
The implementation of the existing rehabilitation so far has been going quite well, although there are still shortcomings to ensure rehabilitation which is influenced by several factors. Factors that affect rehabilitation come from internal as well as from external, including the understanding of investigators and judges related to rehabilitation and narcotics crime, deviations that occur in the implementation of rehabilitation. The purpose of this paper is to describe the rehabilitation carried out by the Lido Narcotics Agency for members of the police. Those caught with narcotics can return to their functions. The research method used a qualitative method which was intended to obtain data regarding the effectiveness of the rehabilitation program carried out by the Lido National Narcotics Agency for members of the Indonesian National Police who were caught with narcotics.